2017
DOI: 10.1111/eff.12371
|View full text |Cite
|
Sign up to set email alerts
|

Migration behaviour and escapement of European silver eels from a large lake and wetland system subject to water level management (Grand‐Lieu Lake, France): New insights from regulated acoustic telemetry data

Abstract: Current knowledge about the downstream migration of sexually mature European eels (Anguilla anguilla) remains incomplete, particularly in still water habitats such as lakes and wetlands subject to water level management. However, for the management of this endangered species, it is important to understand migration dynamics, and contribution to the breeding stock. This study aimed to assess the parameters that trigger and guide the migration of silver eels in the largest floodplain lake and associated wetlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…After a recovery period, and when all anesthetic effects had dispersed (~1h), the fish were released 500 m below the fishing site ( Figure 1) to prevent a second capture. Previous survival tests with eels tagged using the same method showed no death or injury (Trancart et al, 2017); thus, based on the endangered status of European eels, we chose not to perform a survival test for this experiment. We also assumed low natural mortality, as study site is free of potential predators of large silver eels, such as catfish (e.g., Silurus glanis), while grey herons (Ardea cinerea) are unlikely to consume eels of this size, and are limited to foraging along the banks of this river (Feunteun and Marion, 1994).…”
Section: Collection and Tagging Of Silver Eelsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a recovery period, and when all anesthetic effects had dispersed (~1h), the fish were released 500 m below the fishing site ( Figure 1) to prevent a second capture. Previous survival tests with eels tagged using the same method showed no death or injury (Trancart et al, 2017); thus, based on the endangered status of European eels, we chose not to perform a survival test for this experiment. We also assumed low natural mortality, as study site is free of potential predators of large silver eels, such as catfish (e.g., Silurus glanis), while grey herons (Ardea cinerea) are unlikely to consume eels of this size, and are limited to foraging along the banks of this river (Feunteun and Marion, 1994).…”
Section: Collection and Tagging Of Silver Eelsmentioning
confidence: 99%
“…However, other less expected effects also occur frequently. For example, in a highly important floodplain lake in France (Grand-Lieu), a small dam that was installed to regulate water level might contribute to the low escapement rate of silver eels (36%) by reducing their perception of environmental triggers and/or cues, and by disturbing them when gates are open at inappropriate times (Trancart et al, 2017).…”
mentioning
confidence: 99%
“…After a recovery period in a large aerated tank and when all anaesthetic effects had dispersed (full recovery of locomotor movements, usually under 1 hr), the fish were released 100 m downstream of the fishing site, which was located about 3 km upstream of the dam. Previous survival tests with eels from the same study site that were tagged with the same method showed no death or injury (Trancart et al, 2017); thus, based on the endangered status of European eels and the very low number of silver eels in Fremur River, we chose not to perform survival test for this experiment. The institutional and national guides for the care and use of laboratory animals were followed.…”
Section: Silver Eel Collection and Tagging Methodsmentioning
confidence: 99%
“…Similarly, the use of hydrological predictors only should appear restrictive for predicting migration in lagoons, reservoirs, or lakes, where other environmental factors are involved (e.g. water level, wind, coastal current, or atmospheric pressure; Acou et al, 2008;Cullen and McCarthy, 2003;Trancart et al, 2018a;Verbiest et al, 2012). In these contexts, knowledge on migration controls of silver eels should still be deepened through local monitoring surveys before implementing generic and transferable approaches.…”
Section: Modelling Approach and Environmental Predictorsmentioning
confidence: 99%
“…In Europe alone, more than 21 300 hydropower dams have been recorded, and more than 8 700 additional plants are planned or under construction (WWF et al, 2019). However, the triggering and control of silver eels migration are certainly different in lagoons, highly regulated rivers, reservoirs, and lakes where the water level and its variation, together with atmospheric conditions overrule flow regimes (Acou et al, 2008;Feunteun et al, 2000;Trancart et al, 2018a). To ensure the transferability of our models to end-user stakeholders, we compiled the BRT models and prediction functions in an R package named 'silvRpeak', available in Appendix C. Accordingly, information on river flow characteristics (i.e.…”
Section: Management Implication and Transferabilitymentioning
confidence: 99%